Angiographic Characteristics of Cerebral Perfusion and Hemodynamics of the Bridging Artery After Surgical Treatment of Unilateral Moyamoya Disease - Zhang, Kun; Ren, Wei; Sun, Yu-Xue; Wang, Xin-Jun; Li, Chao-Yue; Wang, Zi-Liang; Li, Tian-Xiao; Gao, Bu-Lang (Frontiers in Neuroscience, 2022)
Purpose To investigate the characteristics of cerebral perfusion and hemodynamics of bypass grafting in the treatment of moyamoya disease (MMD) using the iFlow color-coded flow map in comparison with magnetic resonance imaging–perfusion-weighted imaging (MRI–PWI) and computational fluid dynamic (CFD) analysis. Materials and Methods Patients with MMD treated with bypass grafting who had undergone MRI PWI and digital subtraction angiography for iFlow color-coded map was retrospectively enrolled and CFD was performed for calculating the hemodynamic stresses around the bypass grafting. Results Forty-five patients with unilateral MMD treated with bypass surgery were enrolled. The bypass surgery was successful in all patients, with no severe neurological complications during the periprocedural period. Followed up for 4–12 months (median 5.5), the neurological function was good in all patients. The cerebral blood flow (CBF), cerebral blood volume (CBV), mean transit time (MTT), and time to peak (TTP) were significantly (p < 0.05) improved in the middle cerebral artery distribution area on the surgical side before and after vascular bypass, and the difference of TTP (s) measured from the proximal bifurcation of common carotid artery to the confluence of sinus was also significant (p < 0.05). A significant (p < 0.05) positive correlation existed in the perfusion parameters between the iFlow blood perfusion and the MRI–PWI perfusion, with r-value for TTP of 0.765 (p < 0.01). The iFlow color-coded blood flow map showed warm color changes on the diseased side, similar to those on the contralateral side. In CFD analysis, the hemodynamic stresses were all improved, in and around the bypass grafting and distal vessels, which were beneficial to blood flow entering distal arterial branches. Conclusion The iFlow color-coded flow map can be used to analyze cerebral perfusion after bypass grafting for MMD, similar to MRI–PWI, and CFD can be used to analyze the hemodynamics after bypass grafting, revealing improved hemodynamics to promote blood flow entering distal arteries.